Examining supply chain quality management in the Chinese automobile industry - Hu, Jiayao (2017)
The aim of this thesis is to understand what supply chain quality management (SCQM) is and to examine SCQM practices in the Chinese automobile industry by comparing the different SCQM implementation between Chinese Self-owned Brands (CSBs) and Joint Ventures (JVs). This thesis attempts to reveal and understand SCQM practices in order to provide new insights in dealing with quality issues along the supply chain. Hence, in this thesis three research questions (RQs) are explored and answered: RQ1) What are the main factors impacting on SCQM in the Chinese automobile industry? RQ2) What are the differences between CSBs and JVs in the field of SCQM? RQ3) Why do such differences occur?